Students' perceptions towards the use of gamification - Syed Khuzzan Alhabshi, Sh Mazlina; Harun, Nor Zalina; Hanid, Mahanim; Abdullah Habib, Siti Nora Haryati (CA and CC Press AB, 2021)
The Higher education system has been facing some difficulties to attract the millennial generation in engaging within the classroom setting using the traditional face-to-face learning environment, leading to other problematic issues in the long run. Millennial students often get bored, less motivated and lose their focus in the traditional learning environment due to the lack of engagement between students, as well as the instructors/ lecturers. Therefore, Higher Education Institutions (HEIs) are encouraging the use of gamification in education for the purpose of improving the intrinsic motivation as well as engagement. This paper reports the students’ perceptions towards the use of gamification during their class. This study used observation and questionnaire survey towards a group of second year and final year Quantity Surveying students in the International Islamic University Malaysia (IIUM). Eighty-three students responded to the questionnaire. The results showed a positive perception toward the use of gamification in their lecture. Students require effort-demanding, challenging, sophisticated learning systems that increase competency, enhance recall memory, concentration, attentiveness, commitment, and social interaction. Findings from the study shows that gamification was found to promote the student’s engagement in terms of their participation in class, enjoyment throughout the activities as well as their motivational factor to focus in class. Limitations of the study are identified, which highlights the need for further research on the subject area.